Submission to the Special Joint Committee of the Senate and the House of Commons on the Proposed Amendment to Section 93 of the Canadian Constitution - Quebec Federation of Home and School Associations (QFHSA) (1997)
The Quebec Federation of Home & School Associations Inc., (QFHSA) welcomes the opportunity to present this submission to the Special Joint Committee on the proposed amendment to Section 93, sub-sections (1-4) of the Constitution, 1867, concerning the school system in Quebec.

Submission to Secretariat des Commissions Assemblee Nationale on the Place of Religion in Schools - Quebec Federation of Home and School Associations (QFHSA) (1999)
The Report of the Task Force on the Place of Religion in Schools in Quebec and its recommendations have been studied by the QFHSA's Education Committee and discussed with our members within a very restricted time frame. Although there are sections of the report that produced responses to which a majority of the participants were in agreement, there are also sections that produced far more diverse opinions about the nature of this submission.

1999 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1999)

1998 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1998)

1997 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1997)

1996 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1996)

1995 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1995)

1994 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1994)

1993 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1993)

1992 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1992)

1991 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1991)

1990 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1990)